Producing scientific knowledge on migration : perspectives on African and Arab countries - (:unkn) unknown (My University, 2014)
The general objective of this paper is to explore the scientific knowledge produced on the topic of migration in/from African or Arab countries. More specifically, it attempts to identify how different features of the current international division of scientific labour can be illustrated by an examination of the research conducted on migration in/from African and Arab countries. Two main aspects are explored: the role that Arab and African academic communities play in the production of knowledge on migration; and the research priorities among ?Western and non-Western' academics. Articles published between the years 2000 and 2010 in three main journals specialized in migration studies are analysed in order to discuss to a certain extent the setting of a hegemonic scientific agenda on international migration which mainly reflects West European and North American concerns. Two main conclusions are drawn: (1) the quasiabsence of scholars from Arab and African academic institutions in mainstream journals is one of the factors explaining the focus of published research on topics relevant to ?Western' societies (mainly the insertion process in European and North American countries); and (2) important dimensions of migration dynamics in Arab and African countries are being neglected.
Keywords: African Research